General self-efficacy and hypertension treatment adherence in Algerian private clinical settings - Said Kara (AOSIS, 2022)
Background. The purpose of this study was to investigate the connection between self-efficacy and treatment adherence, working on the assumption that self-efficacy plays a role in determining treatment adherence in chronic diseases. Hypertension affects one-third of the world's population. In Africa, hypertension is a leading cause of death from a non-communicable disease. Modifications to lifestyle and behavior, as well as increased access to pharmaceuticals, are necessary for every African nation to bring the prevalence of hypertension and cardiovascular disorders under control. Methods.  In order to assess the predictive association between the two, we conducted research on 216 hypertensive patients who were treated in private clinics in Algeria. These patients were given two assessments to fill out: one was called the general self-efficacy scale (GSES), and the other was called the treatment adherence scale. Comparisons of male and female self-efficacy and adherence were made with the help of Pearson's correlation coefficient and a sample independent t-test (self-efficacy, adherence to treatment). Conclusions.  Self-efficacy in general has been shown to be connected with adherence to hypertension therapy (r(214) = 0.496, p=0.01, 0.05). There is no significant difference between the sexes in either self-efficacy (t(214)=0.985, p=0.326, 0.05) or hypertension treatment adherence (t(214)=0.034, p=0.973, 0.05). A higher level of self-efficacy was found to have a positive correlation with a higher level of treatment adherence; it is possible to increase the medication adherence of hypertension patients by enhancing their level of self-efficacy. It is important for those working in health care to acknowledge the significance that self-care plays in overall health.